The Effect of Serum 25-Hydroxyvitamin D Concentrations on Elevated Serum C-Reactive Protein Concentrations in Normal Weight, Overweight and Obese Participants of a Preventive Health Program - Mastroeni, Silmara S. B. S. (Nutrients, 2016)
The hypothesized effect of vitamin D on C-reactive protein (CRP) has received substantial attention as a potential means to alleviate the risk for cardiovascular disease. However, observational studies have been inconsistent in their reporting of associations between serum 25-hydroxyvitamin D (25(OH)D) and CRP concentrations, and trials and meta analyses have been inconsistent in their conclusions regarding the effect of vitamin D supplementation on CRP concentrations. These supplementation trials were mostly conducted among patients with more or less inflammatory complications and did not consider potential distinctive effects by weight status. To further our understanding of the potential influences of vitamin D on CRP, we analyzed longitudinal observations of 6755 participants of a preventative health program. On average, serum 25(OH)D concentrations increased from 88.3 to 121.0 nmol/L and those of CRP decreased from 1.7 to 1.6 mg/L between baseline and follow up. Relative to obese participants without temporal increases in 25(OH)D, those who showed improvements of <25, 25–50, 50–75, and more than 75 nmol/L at follow up were 0.57 (95% confidence interval: 0.37–0.88), 0.54 (0.34–0.85), 0.49 (0.30–0.80), and 0.48 (0.29–0.78) times as likely to have elevated CRP concentrations (≥1 mg/L), respectively. These associations were less pronounced and not statistically significant for normal weight and overweight participants. Herewith, the findings suggest that promotion of adequate serum 25(OH)D concentrations among obese individuals along with healthy lifestyles may alleviate the public health burden associated with cardiovascular disease.